Experiences of inequality: the meanings of schooling envisaged by poor youths (Educação e Pesquisa, 2006)
In this article I intend to discuss the meanings attributed to the experience of schooling by poor young people from the outskirts of Belo Horizonte who took part in a federal program of social inclusion - the Voluntary Civil Service Program (1996-2002) of the Ministry of Justice and Ministry for Work and Employment. The data and testimonies given were collected through participant observation and the conduction of interviews with youngsters, parents, and professionals (managers, instructors, and coordinators). In one of its phases, I looked into the school experiences of the subjects studied, trying to capture the meanings created, their values and expectations about their schooling. These youngsters had grown up under the impact of increasing social and economic inequalities during the last decades in Brazil. At the same time that they reaped the benefits of the expansion of schooling opportunities for the new generations, they experienced the access to education in an uneven manner. Looking at the subjects of this study, I could see that most of them had had a troubled school trajectory. Although they had more schooling than their parents, they had gone through an uncertain path, full of difficulties, coming in and out of school. At the same time, and despite experiencing situations of social and economic exclusion, the meanings they attributed to schooling are multiple. Education remains as a value for these youngsters, despite the tense and ambiguous relation they maintain with the school institution. They demand a quality school, with clear rules and procedures, but also a school where they are respected and recognized as subjects with rights.